Selective Adsorption of Iron(III) Ions Based on Nickel(II) Oxide-copper(II) Oxide Nanoparticles - Danish, Ekram Y.; Marwani, Hadi M.; Almoslehi, Kholoud F.; Khan, Sher B.; Bakhsh, Esraa M.; Asiri, Abdullah M.; Abozenadah, Hadeel A. (Current Analytical Chemistry, 2022)
Background: Water contamination and its remediation are currently considered a major concern worldwide. Design of effective methods for water purification is highly demanded for the adsorption and removal of such pollutants. Objective: This study depicts the effectiveness of nickel oxide-copper oxide nanoparticles (NiO-CuO), which can extract and remediate ferric ions, Fe(III), from aqueous solutions. Methods: The NiO-CuO nanoparticles were simply prepared by the co-precipitation method and then used as adsorbent with respectable advantages of high uptake capacity and surface area. Results: Adsorption of Fe(III) onto NiO-CuO nanoparticles showed an uptake capacity of 85.86 mgg-1 at pH 5.0. The obtained data from the carried-out experiment of Fe(III) adsorption onto NiO-CuO nanoparticles were well suited to the Langmuir isotherm and pseudo-second-order kinetic models. Moreover, different coexisting ions did not influence the adsorption of Fe(III) onto NiO-CuO nanoparticles. The recommended methodology was implemented on the adsorption and removal of several environmental water samples with high efficiency. Conclusion: The designed method displayed that NiO-CuO nanoparticles can be used as a promising material for the adsorptive removal of heavy metals from water.
Keywords: environmental applications